(untitled) (AYUSHDHARA, 2022)
Human body has a compact systemic organisation of different tissues and organs which is managed by well specified metabolic and homeostatic mechanisms having sensitivity regarding it surroundings microscopically as well as macroscopically. It gets affected by the things around it either inside or outside. Hence while discussing its lives the environment or the climate where it lives comprises great aspect to mention so that appropriate measures regarding maintenance of health conditions can be analysed accordingly. As it has to be seen that the persons fallowing their health monitoring daily regimens also tends to attain several health discomfort or disorders while seen any change the climatic conditions where they live. So, the climatic variations measures to be great factor for human lives. That is why there are several rules and regimens regarding climatic variations are advised since very past time. In Ayurveda it is called as Ritucharya, the Charya or regimens mint for different Ritus or seasons. According to the Ayurveda there are total six seasons (Ritus) in one year and the body needs to adapt itself according to the seasonal variation to remain healthy. But whenever fails to adopt or fails to attain the compulsory consequence results in deformities